MANAGEMENT OF MUCOCELE WITH SURGICAL EXCISION: A CASE REPORT - Pralampito, Firman Musti; Elharis, Mahfuzhi (Universitas Baiturrahmah, 2025)
Background: mucocele is a condition in which mucous secretions accumulate in the sub- epithelial layer originating from the salivary gland and salivary ducts in the oral cavity. Mucocele has two types, namely mucus retention and mucus extravasation. The clinical form of the mucocele is a smooth and asymptomatic lump, blue to pink. Extravasation-type mucocele isthe most common case in pediatric patients. Surgical excision is one of the most common procedures for mucoceles in the oral cavity, and is stated to be the simplest treatment that gives the best results if done correctly.Case report: a 16- year-old female patient came with complaints of a lump on the lower lip that began to be felt 6 months ago, pain when eating and rubbing her teeth. The lump once shrank and released a clear fluid, then enlarged again. Intraoral showed a lump on the lower left labial mucosa of the same color as the surrounding mucosa, unstalked/sessile, ±3 mm in diameter and transparent edges. Management: Surgical excision is performed to remove the entire lesion, accompanied by education so that the causative factors can be eliminated and recurrence can be avoided.Conclusion: surgical excision of the mucocele in this case report was performed with good management of patient behavior and showed good results without excessive fear from the patient.